2015
DOI: 10.1016/j.stem.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Induction and Reversal of Diabetes in Mice Transplanted with Human Embryonic Stem Cell-Derived Pancreatic Endoderm

Abstract: Type 1 diabetes (T1D) is an autoimmune disease caused by T cell-mediated destruction of insulin-producing β cells in the islets of Langerhans. In most cases, reversal of disease would require strategies combining islet cell replacement with immunotherapy that are currently available only for the most severely affected patients. Here, we demonstrate that immunotherapies that target T cell costimulatory pathways block the rejection of xenogeneic human embryonic-stem-cell-derived pancreatic endoderm (hESC-PE) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 59 publications
1
66
0
Order By: Relevance
“…Preclinical studies showed that when hES cell-derived PDX1 + progenitors are transplanted into mice, some of these cells undergo growth and differentiation in vivo into functional β-cells that can reverse diabetes 69,72 . These advances have led to phase I and phase II clinical trials of pancreatic progenitors.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…Preclinical studies showed that when hES cell-derived PDX1 + progenitors are transplanted into mice, some of these cells undergo growth and differentiation in vivo into functional β-cells that can reverse diabetes 69,72 . These advances have led to phase I and phase II clinical trials of pancreatic progenitors.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…The ability of co-stimulation blockade to protect iPSC-derived beta cells from both xenogeneic and allogeneic rejection has been reported (41). Human iPSC-derived beta cells are rapidly rejected when transplanted into immunocompetent mice.…”
Section: Pluripotent Stem Cells and Stem Cell-derived Cell Populationsmentioning
confidence: 99%
“…Coupled with such regenerative strategies, advances in genetic modification of stem cells and iPSCs may soon allow us to engineer thymus or correct defects in order to modulate and enforce tolerance. Although not ready for prime time, these therapeutic strategies have tremendous potential, considering that human embryonic stem cells have recently been used to generate both thymic epithelial progenitors (196,197) and islet-like structures (198,199) that recapitulate the function of their adult differentiated counterparts upon transplantation in mice or humanized models.…”
Section: Stability Of Tregsmentioning
confidence: 99%